A picture of the other in Imam Al-Hassan Al-Mujtaba's speech (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research study examines a linguistic issue that belongs to the field of linguistic studies in its persuasive and communicative dimension, and this issue relates to the disclosure of the manifestations of the image of the other “addressed” recipient, and the mechanism of its application to linguistic texts, which are samples from the Imam Al-Hassan Al-Mujtaba's speech, This research also attempts at compromising both sides of the saying: theoretical and practical. This research deals with the talk about the importance of linguistic and Pragmatics studies and the definition of the theory of reception in its linguistic meaning and idiomatic concept, then moves on to talk about the concept of "addressee other" and their meanings and manifestations in the communicative process, and then the research discusses the image of the other in the speech of Imam Al-Hassan Al-Mujtaba  and its number and how it came Consistent with deliberative purposes, it envisages influencing and persuading the addressees within within the directions of the approach of the Imamate and the Prophet hood. The descriptive and analytical methodology has proved to be the best to Approaching models from the speeches of Imam Hassan Al-Mujtaba ، analyze the processing procedures when studying the linguistic phenomenon، and to unravel the image of the addressee/other from within. يدرس البحث قضيَّةٍ لغويَّةٍ تنتمي إلى حقل الدراسات اللسانيَّة في بعدها الإقناعي التواصلي، وتتعلَّق هذه القضيَّة بالكشف عن تجلِّياتِ صورةِ الآخر "المخاطَب - المتلقِّي"، وآليَّة تطبيقها على نصوصٍ لغويّةٍ، هي نماذج من خطاب الإمام الحسن المجتبى(u)، وقد حاول البحث وَضْعَ مقاربةٍ توضِّح جانبي المقولة: النظريّ، والتطبيقيّ. يتناول هذا البحثُ الحديثَ عن أهمية الدراسات اللسانية والتداولية والتعريف بنظرية التلقي بمعناها اللغوي ومفهومها الاصطلاحي، ثم ينتقل للحديث عن مفهوم "الآخر المخاطَب" ومعانيها وتجلِّياتها في العمليَّة التواصليَّة، وبعد ذلك يناقش البحث صورة الآخر في خطاب الإمام الحسن المجتبى(u) وتعددها، وكيف جاءت موافقة لمقاصد تداوليَّة، تتوخَّى التأثير في المخاطَب وإقناعه ضمن توجُّهات نهج الإمامة والنبوة؛ حيث نتلمَّس فنيَّة الإبداع الخطابي ِّللإمام الحسن (u) وقدرته على تجسيد صورة الآخر ورصد تحولاتها في العملية الخطابية. ولعلَّ المنهجَ الوصفيَّ المشفوعَ بالتحليل يكون الأمثلَ في مقاربة نماذج من خطب الإمام الحسن المجتبى (u)، وتحليل العمليَّات الإجرائيَّة في دراسة الظاهرة اللغويَّة، وكشفِ صورة الآخر "المخاطَب" فيها.